Biological sulphate reduction using lignocellulose hydrolysis by-products produced by fungal hydrolysis of Cenchrus ciliaris cv. Molopo (Buffelsgrass) - Cloete, T.E. (Thomas Eugene), 1958- (University of Pretoria, 2013)
Dissertation (MSc (Microbiology))--University of Pretoria, 2006.